2016
DOI: 10.1016/j.carbon.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Relating the optical absorption coefficient of nanosheet dispersions to the intrinsic monolayer absorption

Abstract: The concentration of nanosheet suspensions is an important technological parameter which is commonly measured by optical spectroscopy using the absorption coefficient to transform absorbance into concentration. However for all 2D materials, the absorption coefficient is poorly known, resulting in potentially large errors in measured concentration. Here we derive an expression relating the optical absorption coefficient of an isotropic ensemble of nanosheets to the intrinsic monolayer absorption. This has allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 52 publications
(34 reference statements)
3
26
0
Order By: Relevance
“…1b, the obtained value for a is 1210 mg -1 m -1 ml and this value is definitely in the range with the previous reported a for surfactant-based graphene [22]. However, we note that the determined value of a in this research work is very far from the proposed theoretical a value of 4237 mg -1 m -1 ml for pristine monolayer graphene [23]. As suggested by theory, the deviation of a may possibly caused by the preparation method, the presence of functional group on graphene sheet and mean thickness of multilayer graphene [24].…”
Section: Validation Of Graphenesupporting
confidence: 73%
“…1b, the obtained value for a is 1210 mg -1 m -1 ml and this value is definitely in the range with the previous reported a for surfactant-based graphene [22]. However, we note that the determined value of a in this research work is very far from the proposed theoretical a value of 4237 mg -1 m -1 ml for pristine monolayer graphene [23]. As suggested by theory, the deviation of a may possibly caused by the preparation method, the presence of functional group on graphene sheet and mean thickness of multilayer graphene [24].…”
Section: Validation Of Graphenesupporting
confidence: 73%
“…particularly clear when an incompletely reduced GO sample is compared, showing a strong increase in absorbance between that of GO and fully reduced GO (Table 1) Absorbance at 808 nm (fixed 1 mg ml -1 ) 4237 @750 nm 46 47.73 7380 @ 265 nm 40 36.68 7380 @ 265 nm 40 28.00 40 6150 @ 230 nm 40 6.08…”
Section: Graphene Productionmentioning
confidence: 99%
“…Shimadzu UV Spectrophotometer via the absorbance at 750 nm using the extinction coefficient 4237 ml mg -1 m -1 determined by Paton et al (Figure 1a). 46 The absorbance spectra for the graphene materials was also measured using a UV-310PC Shimadzu UV-vis-NIR spectrometer.…”
Section: Graphene Suspension Preparation and Characterizationmentioning
confidence: 99%
“…For example, assume a square lattice PhC is designed for the optical bandgap of monolayer molybdenum disulfide (MoS 2 ), i.e. approximately 660 nm [52]; Villeneuve et al in [51] showed that for a rod-type PhC lattice with material index n = 3.4 , a = 1 and r = 0.2a , a H1 cavity would have its cavity mode at λ = 2.56a . In other words, a PhC cavity with a mode at λ = 660 nm , requires its lattice constant to be, a = 258 nm and the radius to be, r = 52 nm , with rod heights of at least 660 nm.…”
Section: Photonic Crystal Cavity Designmentioning
confidence: 99%
“…For a cavity with a Q-factor of 300, such as the rod-type PhC cavity discussed here, a resonating photonic mode inside a cavity is expected to oscillate 300 times before it leaks half of its energy outside the cavity. For a MoS 2 monolayer with an absorption coefficient of 0.05, coupled to a rod-type PhC cavity the absorption of the monolayer can be enhanced to almost unity [52]. This can be calculated using the following equation:…”
Section: Cavity Performancementioning
confidence: 99%